ANALYSIS OF THE QUALITY OF LICENSING SERVICES AT THE INVESTMENT AND ONE-DOOR INTEGRATED SERVICE SERVICE OF SIDOARJO REGENCY - Septikasari, Revi Dwi; Widodo, Joko; Radjikan, Radjikan (MAP Observer: Jurnal Penelitian Administrasi Publik, 2024)
The purpose of this study is to describe and analyze the quality of licensing services at the Sidoarjo District Investment and One-Stop Services Office. The techniques used in this study were observation and interviews. This study uses qualitative research with a descriptive approach. This study focuses on a survey of community satisfaction based on the Regulation of the Minister for Administrative Reform and Bureaucratic Reform Number 14 of 2017 which includes 9 indicators, namely, requirements, systems, mechanisms and procedures, service time, fees or rates, product specifications, type of service, competence of implementers, implementing behavior, handling complaints, suggestions, and input, facilities and infrastructure. The results obtained in this study indicate that the quality of licensing services at the Investment and One-Stop Services Office is good. It’s just that it needs to be improved again on several indicators, namely service time and handling of complaints, suggestions and input. It is hoped that in the future this can be improved, because community satisfaction can determine the excellent quality of public services.